Efektifitas Latihan Fisik Yoga terhadap Kadar Gula Darah Sewaktu pada Diabetes Mellitus Tipe 2 di Kramat Jakarta - Suwarno, Maria Lousiana; Sianturi, Sondang Ratnauli (Jurnal Keperawatan Soedirman, 2017)
Diabetes Mellitus type 2 is the most common type of diabetes is found around the world. It is estimated in the year 2035 will occur explosion sufferers of diabetes mellitus. Diabetes Mellitus not controlled then it may cause complications in organs – other organs such as: heart, kidneys and eyes. There are several treatment Diabetes Mellitus, one of which is the physical exercises of yoga.In this study, aiming to let acquired clarity about the effectiveness of physical yoga exercises against the respondent's blood sugar. This research is quasi alphabets experiment with the design of the intervention group pre test – post test. The Sampling method by using the Krejcie table population size (N) 55 and the number of samples (S) 48. Data analysis with Ordinal Regression and difference test. On this group intervention is done as much as once a week for 3 months.The statistical test used different test pretest and post test. Ordinal regression test results showing that yoga changes have an effect on blood sugar levels while (Pvalue 0.003). On different Wilcoxon test results obtained p 0.006, meaning that there is a difference in blood sugar during before and after physical exercises of yoga. In conclusion, this physical exercise yoga is effective for lowering blood sugar levels while in type 2 DM; then it is recommended that the Ministry of Health introduced this intervention, in the independent care of patients at home, so that patients can control their blood sugar levels.